A SCIENCE FOR ALL? SOME REFLECTIONS ON THE SCIENCIE POPULARIZATION - Mesía Maraví, Rubén (2014)
The article proposes to undertake a reflection on the theme of the popularization of science, namely the need to bring science to large groups of citizen, in the broadest layers of society. As the present has already been made aware of the need for such dissemination of science and its direct impact on social development, you need to comment and discuss the most basic aspects of the subject as, for example, the nomenclature, that is, how to properly call the activity, because the name you provide will depend on the type of actions that are expected to perform the selection of the public to be taken into account, the contents to be taught, and so on. It is also necessary to reflect on how this diffusion has been developed over time, to have a historical perspective to some extent guide the development of actions. Finally, it is necessary to analyze the different strategies that can be used effectively in popularizing, taking into account our own characteristics and possibilities.